Analytical and Comparative Study of a Mini Solar-Powered Cogeneration Unit Based on Organic Rankine cycle for Low-Temperature Applications - Muhsen Habka; Salman Ajib (Global Journal of Energy Technology Research Updates, 2014)
In this paper, we analyze characteristics of a small Combined Heat and Power (CHP) system based mainly on Organic Rankine Cycle (ORC) and heating plant in actual series connection regarding the low-temperature heat carrier heated by purely solar flat collector field. Simultaneously and for specific power production, comparison of this layout with stand-alone ORC, and with the traditional ORC-CHP imposing gain of condenser heat for heating aims, in second step, has been conducted. For evaluation, energetic and design criteria have been determined opposite the heating effects and also temperatures of the heat source and sink. The simulations addressed interesting optimization ratios till 24 % for the power unit throughout this series CHP utility versus single power generation at the same conditions tested. Moreover, the high heat source temperatures and CHP ratios improve the performance of the overall series plant, while the high supply and return temperatures have negative effects. Finally, the ORC-CHP scheme handled here highlights distinctive exploitation aspects and more suitability in wide range of application in comparison to yielding the high-temperature condensation heat of ORC, especially at low ambient temperatures, high supply and heat source temperatures. So, it can be advised to be adopted instead of the two other strategies.